2012
DOI: 10.4103/2152-7806.103023
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex stimulation for facial chronic neuropathic pain: A review of the literature

Abstract: Background:Facial chronic neuropathic pain (FCNP) is a disabling clinical entity, its incidence is increasing within the chronic pain population. There is indication for neuromodulation when conservative treatment fails. Motor cortex stimulation (MCS) has emerged as an alternative in the advanced management of these patients. The aim of this work is to review the worldwide literature on MCS for FCNP.Methods:A PubMed search from 1990 to 2012 was conducted using established MeSH words. A total of 126 relevant ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 117 publications
(195 reference statements)
3
42
0
4
Order By: Relevance
“…Intraoperative cortical stimulation triggers muscle spasms in the upper limb contra-laterally, which confirms the correctness of the position of the electrode. Electromyographic (EMG) stimulation is a routine method used to monitor the accuracy of the selected target [3][4][5][6][7][8][9]. In cases of phantom pain in an upper extremity, neighboring areas are localized, and electrodes are placed between the cortex for the lower extremity and the face.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Intraoperative cortical stimulation triggers muscle spasms in the upper limb contra-laterally, which confirms the correctness of the position of the electrode. Electromyographic (EMG) stimulation is a routine method used to monitor the accuracy of the selected target [3][4][5][6][7][8][9]. In cases of phantom pain in an upper extremity, neighboring areas are localized, and electrodes are placed between the cortex for the lower extremity and the face.…”
Section: Discussionmentioning
confidence: 99%
“…Potential complications of MCS are mainly infections (5.7%), hardware-related problems (5.1%) and seizures; rarely, hematomas, speech disorders or paraesthesias may occur [5,12]. The complication rate is low, amounting to less than 10% [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though it was first reported 46 in 1993 with 60-90% relief in pain intensity for trigeminal neuropathic pain (TNP) the true efficacy is highly controversial and is now only considered as one of the last resorts in the management options. Monsalve 47 evaluated the efficacy of MCS for facial chronic TNP in a systematic review and found that of 126 relevant studies and 118 patients, 100 (84.7%) underwent permanent implantation and 84% of those had good pain relief. Raslan et al 48 reported that 8 of 11 patients underwent permanent implantation and MCS for TNP and 5 continued to experience pain relief at a mean follow up of 33 months.…”
Section: B Sphenopalatine Ganglion Stimulation For Headache and Facimentioning
confidence: 99%